Síndrome de paraganglioma familial: análise clinico-molecular de uma família mineira - Franciele Antonieta Bianchi Leidenz (2014)
Pheocromocytomas (PCC) and paragangliomas (PGL) are rare neuroendocrine tumors arising from chromaffin cells of the adrenal medulla or extra-adrenal paraganglia, sympathetic or parasympathetic, respectively. These tumors have a wide variety of clinical presentation; it depends on their localization, secretory profile and malignant potential. Sympathetic paragangliomas as well as pheochromocytomas usually secrete catecholamines or metanephrines, being clinically functional and causing mostly cardiovascular symptoms. Parasympathetic paragangliomas, which extend along the paravertebral axis, mainly in the head and neck, are usually nonfunctioning tumors; they can be asymptomatic or behave as slow-growing masses, responsible for pain, mass effect, such as dysphagia, dysphonia and dyspnea, depending on their localization. Although PCC and PGL are commonly sporadic tumors, about 30% of them are caused by germline mutations that lead to, up to now, four distinct syndromes, named Paraganglioma Syndromes Types 1 to 4 (PGL 1 to PGL 4), which are associated with mutations in the Succinate Dehydrogenase genes (SDH), a mitochondrial enzymatic complex that plays a role in the electron transport chain and Krebs cycle. One of these syndromes, caused by mutations in the SDHD gene is described in detail in this study. The family from Minas Gerais consists of 10 members, among whom, two were clinically affected, but died prior to the beginning of this study, five are clinically affected and two are children still asymptomatic. The individuals were submitted to a complete clinical examination, including laboratory exams, dosage of catecholamines and metanephrines (both serum and urine), imaging study with Computed Tomography (CT) and fluorine-18 (18F)-fluorodeoxyglucose (FDG)-positron emission tomography (PET/CT) scan, in addition to molecular study of the most disease-related genes. All living individuals of the family were analyzed and presented the same genetic alterations. A missense mutation in exon 1, Trp5X, leads to the transcription of a stop codon, responsible for the phenotype. In addition to this mutation, all affected individuals also showed a second mutation in exon 2 (Pro53Leu) of still uncertain significance. Among these mutations carriers, four are clinically symptomatic, one of them is asymptomatic and has a pheochromocytoma diagnosed by image study. Another two are asymptomatic children not yet submitted to imaging studies due to their young ages and mean age of phenotype presentation. Even though these tumors are usually benign, we demonstrated, using PET imaging, the presence of multiple local metastasis in some members of the family. In this work we were able to completely describe the behavior of a rare disease, familial paraganglioma syndrome, a condition that is yet not entirely understood. We suggested a surgical approach to the family members that were clinically more symptomatic and a conservative approach to the ones presenting mild illness, severe co-morbidities or showed personal preference. Careful clinical and imaging follow-up of the subjects must be done in order to evaluate the disease behavior in the long run. The children carrying the mutations will be followed up at Hospital das Clínicas by an experienced pediatrician and will be submitted periodically to imaging exams to diagnose early tumors and, therefore, decrease the morbid-mortality of this disease.